Children of the Quicksands - Traore, Efua (Nigeria, 2022)
Her lungs were almost bursting and, just when she thought it was over and she was going to die, the quicksands spat her out. She hit hard ground, a sharp pain driving through her head and shoulders. Coughing and gasping for air, it took her a long moment to calm down. At last, still panting, she looked up. She was not in the jungle of Ajao any more. This was a different place...
Keywords: Family; Family Secrets; Juvenile Fiction